Identification of Exhaled Metabolites Correlated with Respiratory Function and Clinical Features in Adult Patients with Cystic Fibrosis by Real-Time Proton Mass Spectrometry - Malika Mustafina; Artemiy Silantyev; Stanislav Krasovskiy; Alexander Chernyak; Zhanna Naumenko; Aleksandr Suvorov; Daria Gognieva; Magomed Abdullaev; Olga Suvorova; Anna Schmidt; Aida Gadzhiakhmedova; Aleksandra Bykova; et al. (Biomolecules)
Cystic fibrosis (CF) is a hereditary disease characterized by the progression of respiratory disorders, especially in adult patients. The purpose of the study was to identify volatile organic compounds (VOCs) as predictors of respiratory dysfunction, chronic respiratory infections of Staphylococcus aureus, Pseudomonas aeruginosa, Burkholderia cepacia, and VOCs associated with severe genotype and highly effective modulator treatment (HEMT). Exhaled breath samples from 102 adults with CF were analyzed using PTR-TOF-MS, obtained during a forced expiratory maneuver and normal quiet breathing. Using cross-validation and building gradient boosting classifiers (XGBoost), the importance of VOCs for functional and clinical outcomes was determined. The presence of the previously identified VOCs indole, phenol, and dimethyl sulfide were metabolic outcomes associated with impaired respiratory function. New VOCs associated with respiratory disorders were methyl acetate, carbamic acid, 1,3-Pentadiene, and 2,3-dimethyl-2-butene; VOCs associated with the above mentioned respiratory pathogens were non-differentiable nitrogen-containing organic compounds m/z = 47.041 (CH5NO)+ and m/z = 44.044 (C2H5NH+), hydrocarbons (cyclopropane, propene) and methanethiol; and VOCs associated with severe CFTR genotype were non-differentiable VOC m/z = 281.053. No significant features associated with the use of HEMT were identified. Early non-invasive determination of VOCs as biomarkers of the severity of CF and specific pathogenic respiratory flora could make it possible to prescribe adequate therapy and assess the prognosis of the disease. However, further larger standardized studies are needed for clinical use.